TAPPING THE OPPORTUNITIES IN AFRICAN GROWTH AND OPPORTUNITY ACT (AGOA) FOR ECONOMIC DEVELOPMENT IN NIGERIA - ADIE, EDWARD IDAGU; OMALE MATTHEW ADOYI (International Studies Journal)
This study called on Nigerian government to explore the chances in the African Growth and Opportunity Act (AGOA) to improve the current economic woes, which have affected her development and global ranking. It derived its data from the secondary sources such as textbooks, articles, journals, etc., and adopted the theory of interdependence as a framework of analysis. From the qualitative analysis of the data stated above, the paper argued that AGOA, which has been in existence since 2000 has a lot of prospects for Nigeria. These opportunities are in the areas of trade and investment, job creation and poverty alleviation, textile industry, where women can own their companies, capacity building and technical assistance, as well the oil sector. Nigeria, even though has continued to remain a beneficiary of AGOA by meeting the yearly eligibility criteria for beneficiary, has not fully utilised these opportunities as it should. It is on this basis that the paper made some recommendations as follows: Nigeria should fully utilise the opportunities in AGOA to develop its economy by exporting more goods to US market; Enabling environment should be created for female citizens to own their business within the textile zone of Kaduna and other places to alleviate their sufferings thereby contributing to the economic development of the country; Nigeria should therefore take advantage of this opportunity to engage with the US to train Nigerian  more businessmen and women in export processing among others.